A formative intervention study of how learner voice and leadership can be developed within a Learner Representative Council (LRC) in an urban combined school, Namibia - Shipopyeni, Salomo S M (Rhodes University, Faculty of Education, Department of Education, 2020)
The Namibian Education system, after the country gained independence, introduced various reforms to ensure the attainment of the educational goals of access, quality, equity and democracy in schools. One of the policies introduced to promote democracy in our schools was The Educational Act 16 of 2001, which gave birth to the establishment of Learners Representatives Councils (LRC) in schools. The LRC body is the legal learner leadership body established to ensure learners are represented in school leadership. However, various studies have revealed that this legal body of learners in many schools has been merely 'rubber-stamping' decisions made by teachers; learners have had very little input in decisions that affect them as learners. Thus, I was prompted to conduct this formative intervention study on learner leadership at an urban combined school in Namibia. Informed by distributed and transformative leadership theories, the study aimed to develop leadership within the LRC members and the needed expansive transformation regarding leadership practices in school. The intention was for learners to be enabled to practice their democratic right in decision-making processes in matters that concerned their schooling and learning. This study was theoretically and analytically framed by second generation CulturalHistorical Activity Theory. The participants included 12 LRC members, the LRC liaison teacher, the class register teacher, three school management team members and the principal. The research method was a case study, underpinned by the critical paradigm to bring about the fundamental expansive transformation in learner leadership practices at the case study school. This qualitative study was divided into two phases, a contextual profiling phase and an intervention phase. Data were generated through document analysis, observation, questionnaires, focus group interviews and Change Laboratory Workshops. The data were generated to answer the over-arching question: How learner voice and leadership can be developed within a Learner Representative Council (LRC) in an urban combined school, Namibia. The data were analysed inductively and abductively. The key findings were: first, there were a variety of understandings of the concept learner leadership; second, the involvement of LRC members in decision-making processes was limited to involvement in organising extracurricular activities and controlling of other learners at school; third, leadership development opportunities for learners at the case study school were only provided through training at the beginning of the year and the LRC carrying out various activities and roles at the case study school. Several challenges that constrained the LRC voice and leadership development were surfaced and, through Change Laboratory Workshops, the participants of the activity system together with me (the researcher-interventionist), identified the expansive learning opportunities to develop leadership amongst Learner Representative Council (LRC) members. In the final analysis, this study will contribute to the production of knowledge on the concept of learner leadership in the context of Namibia. Fellow scholars, professionals, colleagues and policy makers in education are requested to engage with this thesis to contribute to our understanding of this important aspect of our field and speak back to policy.
Keywords: Education, Secondary -- Namibia; Student government -- Namibia -- Case studies; Student participation in administration -- Namibia -- Case studies